FEATURES OF ETIOLOGY AND PATHOGENESIS OF DISORDERS OF TEMPOROMANDIBULAR JOINT, COMPLICATED BY DYSFUNCTION OF MASTICATORY MUSCLES - I.V. Yatsenko; D.S. Avetikov; V.M. Havrylyev; O.S. Ivanytska; N.A. Sokolova; I.V. Boiko (Ukrainian Medical Stomatological Academy, 2016)
Unstable relationships of anatomical structures of temporomandibular joint (TMJ) which lead to its functional impairment is one of poorly studied problems in surgical dentistry. Among numerous theories of TMJ dysfunction, first of all it is necessary to highlight the occlusive and articulation theory. Its supporters believe that the main cause of the disease is the disorder of masticatory apparatus in the loss of teeth, their pathological abrasion and so on. In addition, in the pathogenesis of TMJ disease, complicated by dysfunction of masticatory muscles, chronic emotional stress also plays an important role, as well as its combination with other abovementioned conditions that lead to dysfunction of masticatory muscles. In dental practice as well as in the area of medicine, one should focus not only on local symptoms, but also study the patient's personality traits. It is believed that the majority of dental patients are mentally healthy people. However, according to official WHO researches, the prevalence of neuroses for the past 70 years has increased by 24 times, and mental illness - by 16 times. Large-scale epidemiological surveys found various forms of neurotic disorders in the vast majority of people. Almost all dental patients with high levels of anxiety are noted for emotional instability, lability, tendency to phobias. In addition, the percentage of patients completely free of any mental disorders ("absolutely" or "perfect" healthy individuals) constitute not more than 35% of the number of healthy people. Many members of the so-called "healthy contingent" display numerous features characteristic for the transition from normal to abnormal personality structure. The main difficulty for diagnosis lies in differentiating of borderline and psychosomatic disorders as separate clinical forms, and also in delineating the boundary between them and the norm. A more in-depth examination of dental patients found different premorbid conditions of personality, characterized by the "aggravation" of symptoms such as emotional lability, straightforwardness, uncompromising attitude, vulnerability. Other patients display psychopathic traits, more or less compensated over life. Thus 50% of healthy people are "accentuated personalities" that can be regarded not as an anomaly, but as a predisposition to the development of neuroses. Neurotic symptoms occurred before the diseases of masticatory and speech apparatus. A number of scientists contend that the major factor that draws attention to joint disease is chronic emotional stress (repeated psychic traumas). TMJ pathology is frequently observed in patients who have been under emotional stress, as well as in masked depression and nervous disorders. The main factors that lead to TMJ diseases, complicated by masticatory muscles dysfunction, are chronic emotional stress and repeated psychic traumas.